Association of leisure-time physical activity and sedentary behavior with carotid atherosclerosis morphology: The ARIC carotid-MRI study - Aarti Kumar; Ye Qiao; Bruce Wasserman; Kelley Pettee Gabriel; Pablo Martinez-Amezcua; Erin E. Dooley; Keith M. Diaz; Kelly R. Evenson; A. Richey Sharrett; Yiyi Zhang; Priya Palta (Elsevier, 2023)
Objective: We evaluated the prospective association of midlife leisure-time physical activity (LTPA) and sedentary behavior (SB), and their temporal patterns, with MRI-measured carotid atherosclerotic morphology. Methods: Participants enrolled in the Carotid MRI substudy (2004-2006) of the Atherosclerosis Risk in Communities (ARIC) Study and with self-reported assessments of LTPA and SB at visits 1 (1987-1989) and 3 (1993-1995) were included in this study. LTPA was ascertained using the ARIC/Baecke physical activity questionnaire and categorized according to the American Heart Association's metric of poor, intermediate, or ideal physical activity. SB, measured as TV viewing frequency, was categorized as high, medium, and low. We used multivariable adjusted linear and logistic regression models to examine the associations between midlife (visit 3 only) and persistent (visit 1 to 3) LTPA and TV viewing with carotid artery plaque burden and components. Results: Among the 1,582 (mean age: 59 years, 43% male, 18% Black) participants, 45.7%, 21.7%, and 32.6% reported ideal, intermediate, or poor LTPA, respectively. High TV viewing was reported in 33.8% of participants, with 46.4% and 19.8% reporting medium or low TV viewing, respectively. Compared to poor LTPA, ideal LTPA in midlife was not associated with total wall volume (ß=0.01, 95% CI: -0.01, 0.03), maximum carotid wall thickness (ß=0.06, 95% CI: -0.08, 0.21), normalized wall index (ß=-0.01, 95% CI: -0.03, 0.01), or maximum stenosis (ß=-0.11, 95% CI: -1.98, 1.76). Low or middle, compared to high, TV viewing was also not associated with carotid artery measures of plaque burden. Compared to poor LTPA or high TV viewing, ideal LTPA (odds ratio (OR): 0.82, 95% CI: 0.55, 1.23) and low TV viewing (OR=0.90, 95% CI: 0.56, 1.44) was not associated with odds of lipid core presence, respectively. Conclusion: Overall, this study does not provide strong evidence for an association between LTPA and SB with carotid plaque measures.